Vegetation diversity and composition, and forage production of natural pasture in East Luwu District, South Sulawesi, Indonesia - SEMA SEMA; JASMAL AHMARI SYAMSU; AMBO AKO; RINDUWATI RINDUWATI (Society for Indonesian Biodiversity, 2025)
Abstract. Sema, Syamsu JA, Ako A, Rinduwati. 2025. Vegetation diversity and composition, and forage production of natural pasture in East Luwu District, South Sulawesi, Indonesia. Biodiversitas 26: 2410-2415. Increasing the productivity of ruminants should be supported by the availability of forage. In the context of pasture, forage availability is determined by type of vegetation and the amount of production in the area so that it can meet the needs of livestock. Research related to forage plant vegetation in South Sulawesi, Indonesia, have been carried out, but more nuanced study is needed to account specific context of biophysical conditions. This study aims to determine the types of vegetation and forage production in a natural pasture in Malili Sub-district, East Luwu District, South Sulawesi. Data was collected by establishing 20 sampling plots with a size 1x1 m, totalling a sampled area of one hectare. Types of vegetation and forage production were measured using the Summed Dominance Ratio method based on frequency, density, and cover area. The result showed that the botanical composition of the sampled pasture based on Dry Weight Rank consisted of 30.00% grass, 15.00% legumes and 55.00% weeds. The pasture comprised of 21 species of grass, 7 species of legumes and 21 species of weeds with three dominant grass species were Cynodon dactylon (5.12%), Epidendrum culculatum (3.59%) and Mecardonia procumbens (3.44%). The carrying capacity of the pasture was 0.16 AU/hectare/month or equivalent to 1,75 AU/hectare/year. The results of this study indicate that the productivity of the existing pasture is relatively low and special efforts are needed to improve its quality.